2018
DOI: 10.5935/1518-0557.20180055
|View full text |Cite
|
Sign up to set email alerts
|

Seminal profile of 23,504 patients over the years: 7 years of experience

Abstract: ObjectiveTo evaluate the behavior of seminal parameters over the years - 2010 to May 2017.MethodsA retrospective study, carried out from January 2010 to May 2017, covering men who underwent sperm examination. Seminal parameters (volume, sperm concentration, motility, morphology, age and duration of infertility in years) of 23,504 men were evaluated. The groups were compared to each other to check whether there were changes to the seminal parameters in that period.ResultsThere was no change over the years consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Furthermore, a reduction in sperm motility was observed from about 26% to 8.5% over a period of time (Geoffroy-Siraudin et al, 2012;Oliveira, et al, 2014). Sperm motility was lower than that reported in men from different countries like Brazilian sub-fertile men (Nogueira et al, 2018), and ejaculates of Italian (Manna et al, 2020) and Indian males (Mukhopadhyay et al, 2010), but was similar to the results reported in India (Camila et al, 2018). Such differences could be attributed to racial, geographical, cultural, environmental, genetic, hormonal, nutritional, or lifestyle variations.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, a reduction in sperm motility was observed from about 26% to 8.5% over a period of time (Geoffroy-Siraudin et al, 2012;Oliveira, et al, 2014). Sperm motility was lower than that reported in men from different countries like Brazilian sub-fertile men (Nogueira et al, 2018), and ejaculates of Italian (Manna et al, 2020) and Indian males (Mukhopadhyay et al, 2010), but was similar to the results reported in India (Camila et al, 2018). Such differences could be attributed to racial, geographical, cultural, environmental, genetic, hormonal, nutritional, or lifestyle variations.…”
Section: Discussionsupporting
confidence: 55%
“…Also in Sao Paolo, semen data from 23,504 infertile men were evaluated over 7.5 years from 2010 to 2017 according to WHO 2010 guidelines 17 , 92 . A decreasing trend of 0.05 ml in seminal volume was observed over the period, alongside a tendency towards reduction in sperm concentration by 1 × 10 6 /ml over the 7.5 years (mean of 34.3 × 10 6 /ml).…”
Section: Temporal Trends In Human Semen Qualitymentioning
confidence: 99%
“…This is due to the fact that various causes of infertility can be bypassed by the use of ART; however frequently the primary condition remains untreated. While female infertility has drawn more attention, it is proposed that 1 in 20 men are infertile on worldwide scale [1]. Moreover, the cause of infertility in about 20% -40% of infertile couples is attributed to the male partner [2].…”
Section: Introductionmentioning
confidence: 99%